Pengembangan Karakter Pada Profil Pelajar Pancasila? - Nugraha, Eric Septian; Jahroni, Ahmad; Hakim, Kaka Luqman (Journal of Information Systems and Management (JISMA), 2024)
The purpose of this study is to find out about the pancasila student profile. The study report USES a descriptive qualitative method by doing note notes because of data generated by listening to oral narratives from youtube channel learn the digital era "resume day 3! Profile of pancasila student and the pancasila student's strengthening project "set out by lina wijayanti. The results of this study explain education not only relating to academic knowledge, but also involve developing the character of learners. Character education aims to establish good attitudes, values, and behavior in learners. The pancasila student profile can be a comprehensive framework for guiding learners in developing good character. Through values - the values contained in the profile of the pancasila learner, learners are expected to be a young generation of people who not only possess intellectual intelligence but also have character learners according to the pancasila values.